Basidiobolomycosis - An unsightly devastating condition, ironically responsive to inexpensive medications: A case report with review of literature - N Naresh Kumar; D Suresh Chelliah; P Meganathan; D Senguttuvan; Skanda Shyamsundar (Wolters Kluwer Medknow Publications, 2023)
Background: Basidiobolomycosis is an infection which results in an indolent, nonhealing, penetrating, unsightly destruction of subcutaneous tissues, rarely described in children. Clinical Description:A 6-year-old girl with no prior medical illness, presented with low-grade intermittent fever associated with an indurated swelling on the posterior aspect of her right leg, which gradually progressed over a period of 6 months into a deep, spreading, nonhealing ulcer, causing pain and restriction of movement. Management and Outcome: Routine blood investigations and swab cultures ruled out pyogenic infections and tuberculosis. She was negative for HIV. The wound was debrided, but there was poor response to antibiotics, fluconazole, and amphotericin B. Biopsy of debrided tissue revealed subcutaneous basidiobolomycosis. She was then treated with a combination of potassium iodide and cotrimoxazole. Over a 3-month period, the ulcer began granulating, and complete resolution was achieved through split-thickness skin grafting. Conclusion: Although uncommon, basidiobolomycosis may be considered in the evaluation of nonhealing penetrating ulcers, especially in immunocompetent children. Rather than expensive antifungals, potassium iodide and cotrimoxazole yield gratifying results in this condition.